Immediate effects on plantar pressure time integral with thermoplastic polyurethane versus plastazote insoles in type 2 diabetes with peripheral neuropathy: A randomized comparative study - Nyoman Chandra Adidharma; I Putu Alit Pawana; Lydia Arfianti; Inggar Narasinta; Sony Wibisono Mudjanarko; Atika; Fahrin Ramadan Andiwijaya (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: The prevalence of diabetes continues to rise worldwide, and diabetic foot ulcers remain a serious complication caused by repeated pressure on the tissue of the sole of the foot due to neuropathy. This study aimed to compare the immediate changes in the plantar pressure time integral (PTI) following the use of Plastazote shoe insoles versus thermoplastic polyurethane (TPU) shoe insoles in adults with type 2 diabetes and peripheral neuropathy. Methods: This study was a randomized, two-group pre-post design study. A total of 24 subjects with type 2 diabetes mellitus were divided into two groups of Plastazote insole group (n = 12) and the TPU insole group (n = 12). PTI was measured using a dynamic plantar pressure measurement system that divided the foot into five regions (heel, midfoot, forefoot, big toe, and toes) before and after insole use. Analyses were performed within groups (pre-post comparison) and between groups (ΔPTI comparison). Safety and user perception were evaluated using a pain VAS during insole use. Results: TPU resulted in a greater reduction in PTI compared to Plastazote in the rear and middle sections of the foot (p ≤ 0.043) as well as in total PTI (p = 0.019), while Plastazote increased PTI in the front section of the foot and total PTI (p ≤ 0.047; p < 0.001). The between-group difference favored TPU (p ≤ 0.024), with no effect on the big toe or other toes (p ≥ 0.721). Conclusion: In patients with type 2 diabetes, the highest plantar pressure is found in the heel and forefoot. The distribution of plantar pressure in type 2 diabetes is influenced more by dynamic factors and neuropathy than by static foot position. Therefore, screening for diabetic foot complications should incorporate static, dynamic, and sensorimotor assessments.